2018
DOI: 10.1007/s11120-018-0551-7
|View full text |Cite
|
Sign up to set email alerts
|

Non-photochemical quenching-dependent acclimation and thylakoid organization of Chlamydomonas reinhardtii to high light stress

Abstract: Light is essential for all photosynthetic organisms while an excess of it can lead to damage mainly the photosystems of the thylakoid membrane. In this study, we have grown Chlamydomonas reinhardtii cells in different intensities of high light to understand the photosynthetic process with reference to thylakoid membrane organization during its acclimation process. We observed, the cells acclimatized to long-term response to high light intensities of 500 and 1000 µmol m s with faster growth and more biomass pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 66 publications
3
18
0
Order By: Relevance
“…During photosynthesis, some of the unused light energy is dissipated. Y (NPQ) reflects the dissipation of excess light energy in the form of heat, representing photoprotection (Nama et al, 2018). Y (NO) indicates the excess light energy not lost to heat dissipation, representing photodamage (Christof Klughammer, 2008;Erhard and Schreiber, 2008;Nama et al, 2018).…”
Section: Nivalis Maintains Robust Photosynthetic Activity At Low Tmentioning
confidence: 99%
“…During photosynthesis, some of the unused light energy is dissipated. Y (NPQ) reflects the dissipation of excess light energy in the form of heat, representing photoprotection (Nama et al, 2018). Y (NO) indicates the excess light energy not lost to heat dissipation, representing photodamage (Christof Klughammer, 2008;Erhard and Schreiber, 2008;Nama et al, 2018).…”
Section: Nivalis Maintains Robust Photosynthetic Activity At Low Tmentioning
confidence: 99%
“…Continuous light exposure leads accumulation of biomass and the cellular over reduction and formation of ROS, which induced autophagy and lipids in microalgae (Shi et al, 2017). Our previous results indicate that PSI and PSII were damaged when cells were grown in high light (Nama et al, 2019 andYadav et al, 2020). Based on this result, we interpret that lipid accumulation in mutant strains could be explained that PSII or PSI is over reduce, which led to high ROS production.…”
Section: High Light Induces the Ros And Autophagy In Chlamydomonasmentioning
confidence: 74%
“…Recently, we reported that the photosynthetic activity was severely affected in pgrl1 and pgr5 of C. reinhardtii when the cells were grown in high light (Yadav et al, 2020). We have also observed the non-photochemical quenching is substantially reduced in pgr5, which is supposed to protect the algae from high light that could harmlessly dissipate excess excitation energy as heat (Nama et al, 2019). The pgr5 cells were much more sensitive to high light (500 µmol photons m -2 s -1 ) when they grow in photoautotrophic conditions.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Primary antibodies were diluted as follows: PsaA (1:5,000); CP47 (1:1,000); LHCSR1 (1:1,000); LHCSR3 (1:4,000); LHCBM5 (1:5,000), which reacts with the three major LHCBMs (e.g. Nama et al, 2019; https://www.agrisera.com/en/ artiklar/lhcbm5-.html); ATPC (1:2,000); and Cyt f (1:3,000). All antibodies were from Agrisera (Sweden).…”
Section: Biochemistrymentioning
confidence: 99%